Excavations at Dun Vulan : a correction - Pearson, Mike Parker
In June 1998, we published a discussion on the interpretation of Iron Age Scottish brochs and wheelhouses. Gilmour & Cook challenged the ideas published by Parker Pearson et al. in 1996. Here, that challenge is taken up.